'In perfect harmony with the spirit of the age': The Oxford University Wesley Guild, 1883–1914. (3rd June 2019) - Wellings, Martin
Abstract : From the middle of the nineteenth century, educational opportunities at the older English universities were gradually extended beyond the limits of the Church of England, first with the abolition of the university tests and then with the opening of higher degrees to Nonconformists. Wesleyan Methodists were keen to take advantage of this new situation, and also to safeguard their young people from non-Methodist influences. A student organization was established in Oxford in 1883, closely linked to the city centre chapel and its ministers, and this Wesley Guild (later the Wesley Society, and then the John Wesley Society) formed the heart of Methodist involvement with the university's undergraduates for the next century. The article explores the background to the guild and its development in the years up to the First World War, using it as a case study for the engagement of Methodism with higher education in this period.